Readiness of Elementary Teachers in Minimum Competency Assessment: Teachers' Competence in Arranging Literature and Numeration Tests - Titis Angga Rini; Puri Selfi Cholifah; Ni Luh Sakinah Nuraini; Kay Margetts (Universitas Muhammadiyah Surakarta, 2021)
Minimum competency assessment is a new challenge for classroom teachers in implementing and integrating it in learning to maximize its diagnostic and curative function on the quality of Indonesian education. This is the background of this research to analyze the readiness of teachers in arranging literacy and numeracy tests in elementary schools. This study used a content analysis design to reveal a test prepared by elementary school teachers for minimum competency assessment involving 30 elementary school teachers. Data analysis results are presented in the form of percentage accuracy of items with quantitative descriptive and examples of items that are described qualitatively. The results showed that the competence of school teachers in compiling literacy and numeracy assessment questions in elementary schools was still not optimal in terms of form, content, context, and cognitive level, especially for reflect and evaluate levels for literacy assessments and reasoning levels for required numeracy assessments. Especially for literary content on literacy, scientific context on literacy and numeracy, and third-level literacy and numeracy. Based on the results of the study, it can be concluded that the competency of elementary school teachers in implementing a minimum competency assessment needs to be carried out to meet the standards and functions of the Indonesian national assessment. This study provides an overview of teacher readiness in carrying out minimum competency assessments in elementary schools related to their role as learning evaluators